Early Markers of Atherosclerotic Disease in Individuals with Excess Weight and Dyslipidemia - Menti,Eduardo (2016)
Abstract Background: Excessive weight is a cardiovascular risk factor since it generates a chronic inflammatory process that aggravates the endothelial function. Objective: To evaluate the endothelial function in individuals with excess weight and mild dyslipidemia using brachial artery flow-mediated dilation (BAFMD), and the association of endothelial function with anthropometric and biochemical variables. Methods: Cross-sectional study that included 74 individuals and evaluated anthropometric variables (body mass index [BMI], waist-hip ratio [WHR], waist circumference [AC], and percentage of body fat [PBF]), biochemical (blood glucose, insulinemia, ultrasensitive C-reactive protein, fibrinogen, total cholesterol, HDL-cholesterol, triglycerides, and LDL-cholesterol) and endothelial function (BAFMD, evaluated by ultrasound). The statistical analysis was performed with SPSS, version 16.0. To study the association between the variables, we used chi-square, Student's t and Mann-Whitney tests, and Pearson's correlation. Logistic regression analyzed the independent influence of the factors. Values of p < 0.05 were considered significant. Results: The participants had a mean age of 50.8 years, and 57% were female. BMI, WC, WHR, and PBF showed no significant association with BAFMD. The male gender (p = 0.02) and higher serum levels of fibrinogen (p = 0.02) were significantly and independently associated with a BAFMD below 8%. Conclusions: In individuals with excess weight and mild untreated dyslipidemia, male gender and higher levels of fibrinogen were independently associated with worse BAFMD.